Comparing Soil Erosion Rates on Terraced and Sloping Cultivated Land in Palestine Using FRN 137Cs Trace - Orwa Houshia; Moncef Benmansour; Lionel Mabit; Emil Fulajtár; Saber Abu-Jabal; Ismail Hroub; Rafat Odeh (International Journal of Analytical Chemistry)
Soil erosion is a serious problem in Palestine. It is enhanced mainly by poor farming practices used in upland agricultural areas occupying the Central Highland of Palestine. The objective of this study is to assess the impact of terracing on soil erosion and deposition rates in the Al-Yamoun area (the Northern West Bank) using the fallout radionuclides cesium -137 (FRN 137Cs). The FRN 137Cs technique, which has proved its efficiency in estimating erosion rates over the last 50–60 years, was used for the first time in Palestine to measure rates of erosion and deposition. The activity of 137Cs was measured by gamma spectrometry using an HPGe detector. For the reference site, the 137Cs inventories ranged between 2499 and 4086 Bq/m2. The average value of the reference site is 3315 ± 410 Bq/m2, which corresponds to a coefficient of variance of 12%, suggesting that the reference site is well representative for estimating 137Cs fallout. This 137Cs amount is too high for bomb-derived fallout and indicates that a significant part of the deposition is from the Chernobyl accident. The 137Cs inventories at both studied sites (terrace site and foot slope site) are significantly lower than those of the reference site. For the terrace site, the inventories are found between 1707 and 2749 Bq/m2, while for the slope site they are between 1050 and 2617 Bq/m2. The lower 137Cs values at both studied sites than values at the reference site indicate that the entire areas of both study sites are eroded and no depositional activity occurs.